A Wittig-olefination–Claisen-rearrangement approach to the 3-methylquinoline-4-carbaldehyde synthesis - Kulkarni, Mukund G.; Desai, Mayur P.; Birhade, Deekshaputra R.; Shaikh, Yunus B.; Dhatrak, Ajit N.; Gannimani, Ramesh (Beilstein Journal of Organic Chemistry, 2012)
Efficient syntheses are described for the synthetically important 3-methylquinoline-4-carbaldehydes 6a–h from o-nitrobenzaldehydes 1a–h employing a Wittig-olefination–Claisen-rearrangement protocol. The Wittig reaction of o-nitrobenzaldehydes with crotyloxymethylene triphenylphosphorane afforded crotyl vinyl ethers 2a–h, which on heating under reflux in xylene underwent Claisen rearrangement to give 4-pentenals 3a–h. Protection of the aldehyde group of the 4-pentenals as acetals 4a–h and subsequent oxidative cleavage of the terminal olefin furnished nitroaldehydes 5a–h. Reductive cyclization of these nitroaldehydes yielded the required 3-methylquinoline-4-carbaldehydes 6a–h in excellent yields. Therefore, an efficient method was developed for the preparation of 3-methylquinoline-4-carbaldehydes from o-nitrobenzaldehydes in a simple five-step procedure.
Keywords: acetal; Claisen rearrangement; oxidative cleavage; ring-closure; Wittig olefination